Readiness of Students to Do Assignments During the Covid-19 Pandemic - Dinda Jengtika Reski; Asmidir Ilyas (Current Issues in Counseling, 2021)
Readiness to learn is the overall condition of a person that makes him ready to respond or answer in the learning process. The learning process will run well if it is supported by several things, including: readiness to learn, doing assignments, reading, and so on. This study aims to: (1) describe the level of readiness of students to do assignments, (2) describe the form of student difficulties in doing assignments, and (3) the role of counseling teachers to overcome student difficulties in doing assignments at SMA N 11 Padang. This research uses a quantitative approach with descriptive research methods. The research subjects were students of SMA N 11 Padang at grade X and XI, totaling 224 people. Collecting data using a Likert scale model questionnaire, data were analyzed using percentage analysis techniques. The results revealed that: (1) the readiness of students to do assignments in the aspect of understanding the task was in the sufficiently ready category with an achievement score of 60.7%, (2) the readiness of students to do assignments in the aspect of providing resources was in the sufficiently ready category with an achievement score of 62, 5%, (3) the readiness of students to do assignments in the task completion aspect is in the sufficiently ready category with an achievement score of 57.6%, (4) the readiness of students to do assignments in the assignment aspect is in the sufficiently ready category with an achievement score of 70%.